2022
DOI: 10.1097/01.asw.0000833608.27136.d1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Occurrence and Healing of Umbilical Pilonidal Sinus: A Rare Clinical Entity

Abstract: Objective: Pilonidal sinus disease (PSD) is a chronic inflammatory condition of skin that is thought to be related to implanted loose hair. Although PSD is most frequently seen in the sacrococcygeal region, it can also occur at the axilla, perineum, suprapubic regions, hands, and umbilicus. The aim of this project was to find factors influencing the development and treatment of umbilical PSD. Methods:In this retrospective study, the authors evaluated 82 patients (19 women, 63 men) with a history of umbilical P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Diagnostic criteria for thyroid fine-needle aspiration were based on the guidelines of the Papanicolaou Society of Cytopathology, and divided into six types: (1) undiagnosed: there is a problem of sampling, so the cytological diagnosis cannot be carried out; (2) benign lesions: nonneoplastic diseases; (3) follicular lesions: tend to be benign lesions, but the possibility of tumors is not ruled out; (4) follicular tumors: adenoma or carcinoma; (5) suspected malignancy: have malignant cytological features, and undiagnosed; (6) malignant tumors [12].…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic criteria for thyroid fine-needle aspiration were based on the guidelines of the Papanicolaou Society of Cytopathology, and divided into six types: (1) undiagnosed: there is a problem of sampling, so the cytological diagnosis cannot be carried out; (2) benign lesions: nonneoplastic diseases; (3) follicular lesions: tend to be benign lesions, but the possibility of tumors is not ruled out; (4) follicular tumors: adenoma or carcinoma; (5) suspected malignancy: have malignant cytological features, and undiagnosed; (6) malignant tumors [12].…”
Section: Patientsmentioning
confidence: 99%
“…In clinical diagnosis of thyroid nodules, the thyroid fine-needle aspiration method is commonly used. This method has the advantages of high safety, simple operation and low cost, and can accurately determine the nature of thyroid nodules, timely detect thyroid malignant tumors, and avoid surgical treatment for benign thyroid patients [3][4][5]. Numerous studies showed that microRNAs (miRNAs) and human cyclin D2 (CCND2) are implicated in tumorigenesis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…pilonidal sinus disease), previous laparoscopy or umbilical surgery and previously burned or hyperpigmented umbilicus. 10 Additionally, prepubertal or postmenopausal patients were also excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
“…A number of clinical evidence was suggested at genetic, metabolism, therapeutic and nutrition levels after growing clinical study. [17][18][19][20][21] System comparisons and integration can help these discoveries. We may learn more about this mystery event in medicine and techniques in the future.…”
Section: Histological Evidencementioning
confidence: 99%